PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN SAINS DENGAN MATERI SIFAT WUJUD BENDA DAN PERUBAHANNYA : Penelitian Tindakkan Kelas Pada Siswa Kls IV di SDN Bakti Winaya Buah Batu Bandung Semester 1 Tahun pelajaran 2012/2013 - Sugiharto, Agung (2013)
Abstrak The Application of the Method of Inkuiry to Improve Student Learning Outcomes in Science Learning With The Material Properties Of Objects And Changes Shape.This Research is based on observations at the fourth grade student at SDN BaktiWinaya Bandung, which shows the result of student learning in science subjects is low. This is because students are not mastering science consepts correctly, because the learning that occurs more often carried out by the menthod of verbal lecture from the theacher to the student. The method used by the authors in this study was classroom action research (CAR), which was developed by KemmisandTaggart. Each cycle consists of four stages : planning, implementation, observation and reflection. The study consisted of two cycles of the material properties of objects and changes shape. The instrument used in this study were student work sheet (LKS), test, observation sheets. Researches can explain that learning uotcomes of students in learning science in the material properties of objects and theirs changes by using the inquiry method is improved by an average value of 67,36 in the first cycle and the second cycle 82,64. With the improvemen of learning outcomes at each cyclical, it can be concluded that learning science with the material properties of objects and changes shape throught inquiry method can improve student leraninguotcomes. Abstrak Meningkatkan Hasil Belajar Sains Dengan Menggunakan Metode Inkuiri. Penelitian ini didasarihasil belajar siswa pada pelajaran IPA yang rendah, karenasiswa kurang menguasai konsep-konsep IPA dengan benar, karena pembelajaransering dilaksanakan secara verbalisme/ceramah. Untukmeningkatkanhasilbelajar, metode yang digunakanadalah Penelitian Tindakan Kelas (PTK), terdiri dari dua siklusdengan materi sifat wujud benda dan perubahannya, Instrumennyaadalah lembar kerja siswa (LKS),tes, lembar observasi. Peneliti menjelaskan bahwa hasil belajar siswa dalam pembelajaran IPA pada materi sifat benda dan perubahannya dengan menggunakan metode inkuirimeningkatdengan rata-rata nilai pada siklus I 67.36, dan pada siklus II 82.64. Kata Kunci :hasil, belajar, sains, inkuiri